2021
DOI: 10.1126/science.abk1603
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent atom-transfer radical cyclization by engineered cytochromes P450

Abstract: Radical cyclization made easy Metalloenzymes contain metal cofactors that can sometimes be exploited to catalyze reactions distinct from their natural function. Drawing on inspiration from heme-based radical polymerizations, Zhou et al . screened a panel of metalloproteins for candidates that could catalyze an atom-transfer radical cyclization, producing a lactam from an amide substrate bearing bromoalkyl and alkene functional groups (see the Perspective by Zhang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 100 publications
0
59
0
Order By: Relevance
“…It must be noted that SET can occur from different combinations of photoexcited states of the catalyst as long as the average redox potential is ∼1.83 V (see the Supporting Information for detailed discussion). Finally, we applied Marcus theory to estimate the barrier for electron transfer from 1 to Mes-Acr* + to generate the radical cation 1 •+ . The four-point approximation was used to calculate the inner sphere reorganization energies, and a modified two sphere model was applied to the outer sphere reorganization energies. From this analysis, we found that TS-SET is ∼0.2 kcal/mol uphill from 1 + Mes-Acr *+ (∼13.9 kcal/mol relative to 1 •+ + Mes-Acr• , the arbitrary zero in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…It must be noted that SET can occur from different combinations of photoexcited states of the catalyst as long as the average redox potential is ∼1.83 V (see the Supporting Information for detailed discussion). Finally, we applied Marcus theory to estimate the barrier for electron transfer from 1 to Mes-Acr* + to generate the radical cation 1 •+ . The four-point approximation was used to calculate the inner sphere reorganization energies, and a modified two sphere model was applied to the outer sphere reorganization energies. From this analysis, we found that TS-SET is ∼0.2 kcal/mol uphill from 1 + Mes-Acr *+ (∼13.9 kcal/mol relative to 1 •+ + Mes-Acr• , the arbitrary zero in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that no stereoselectivity is observed in Enz‐ATRP suggests that polymerization mainly occurs in solution, and not in the enzyme cavity. Although, exciting enantioselectivity has been reported for radical reactions catalyzed by photoenzymes and metalloproteins, [33a,c, 60] stereoselectivity remains elusive, to date, and a grand challenge in Enz‐RDRP.…”
Section: Perspectives and Outlookmentioning
confidence: 99%
“…In addition, the chemistry, using a diazoacetate to generate the Fe-bound carbene, does not have a known analog in biological chemistry (Liu and Arnold, 2021). This result has been built on in recent examples, including engineered cytochrome P450 catalyzed atom transfer radical cyclization (ATRC), where a new C-C bond and a new C-Halogen bond are formed (Zhou et al, 2021). In a further recent development from the Arnold lab, they report the P450 catalyzed enantioselective ring expansion of aziridines to azetidines (Miller et al, 2022).…”
Section: Future Challenges and Outlookmentioning
confidence: 99%